O-018 New Evidence for Structural Brain Differences in Pediatric Crohn's Disease: Impact of Underlying Disease Factors. (March 2016) - Mrakotsky, Christine; Anand, Rajsavi; Watson, Christopher; Vu, Catherine; Matos, Alana; Friel, Shelby; Rivkin, Michael; Snapper, Scott
Abstract : Background: Structural brain changes in gray matter volume, cortical thickness, and white matter density have been recently found in adults with Crohn's disease (CD), with the potential to affect cognitive and emotional functions. Intestinal and systemic inflammation during active disease as well as anti-inflammatory steroid therapy have been considered as possible underlying mechanisms, however to date there is little data for other disease factors, particularly in pediatric CD. We previously demonstrated decreased white matter density, cortical thickness and subcortical volume in a small sample of children with CD compared to healthy controls with independent effects of inflammation and steroids (Mrakotsky et al., 2012, 2013, 2015). We also found inflammation associated with poorer cognition and mood, and CD patients to report poorer school function. This CCFA SRA aims to replicate earlier findings of brain involvement in a larger independent sample of pediatric CD patients. Methods: Structural magnetic resonance and diffusion tensor imaging (MRI, DTI) was performed in 34 children age 10 to 14 years (CD patients: n = 25, age-and sex-matched healthy controls: n = 10) using a 3 Tesla Siemens Trio MRI system. Anatomical whole brain T1-weighted images were acquired at 1 mm 3 voxel size. Diffusion-weighted images were acquired using simultaneous multislice echo planar imaging (2 mm 3 voxel size, 70 directions). All subjects also underwent neuropsychological assessments (tests of attention, memory, IQ, emotional functions), disease severity ratings (HBAI), and phlebotomy to obtain inflammatory markers. CD patients were scanned and tested during an active disease flare or in clinical remission. Cortical thickness and volume was measured using Freesurfer, average fractional anisotropy (FA) reflecting white matter fiber density was computed for several fiber tracts with TBSS. Analyses were adjusted for age, sex, and intracranial volume, and included correlation, regression and group comparisons. Groups were comparable on demographics. Results: Compared to controls, CD patients showed once again widespread reduced cortical thickness in posterior regions (bilateral inferior parietal, superior parietal, supramarginal [<0.001–0.01]) and middle frontal gyrus (<0.05), reduced subcortical volume (bilateral putamen, hippocampi, and right thalamus [<0.01–0.05]) altered FA in limbic tracts (cingulate, uncinate fasciculus [<0.05]) and poorer verbal memory and cognitive function. Inflammation during active disease was associated with cortical thinning (<0.001–0.05), lower FA, (<0.05), and poorer memory and cognition (<0.05–0.01), although direct relationship between brain structure and function was less clear. In addition, higher disease severity and steroid medication was negatively associated with brain structures (<0.001–0.05), as was lifetime use of steroids. Infliximab and chemotherapeutic medication were not significant contributors in this sample. Conclusions: These results confirm our prior findings of both disease and treatment on gray and white matter structures in pediatric CD, suggesting brain involvement as an extraintestinal manifestation of CD. The posterior brain regions implicated mediate higher cognitive and emotional processes and are potentially linked to poorer function in these areas. Current multi array analysis will provide further insight into pathways by which inflammation and disease process transmits to brain and behavior, with the goal to inform medical and psychological therapies.